Associated Factors of Quality of Life in Hypertensive Patients: A Cross-Sectional Study in Riau Province, Indonesia - Maybelliano, Dhimas; Rajunitrigo, Rajunitrigo; Lita, Lita; hamid, abdurrahman; Rasyid, T Abdur (Jurnal Epidemiologi Kesehatan Indonesia, 2026)
Hypertension is a chronic condition that adversely affects quality of life (QoL). Identifying factors associated with QoL is essential for improving hypertension management. This study aimed to identify factors associated with QoL among hypertensive patients in Riau Province, Indonesia. A cross-sectional study was conducted from December 2024 to January 2025 at two public health centers in Riau Province: Puskesmas Rejosari in Pekanbaru City and Puskesmas Bagansiapi-api in Rokan Hilir Regency. A total of 150 hypertensive patients aged 25-59 years were enrolled. QoL was assessed using the WHOQOL-BREF questionnaire. Independent variables included sociodemographic characteristics, comorbidities, dietary patterns, and physical activity. Data were analyzed using univariate analysis, Chi-square test for bivariate associations, and modified Cox regression for multivariable analysis. Among the respondents, 52.0% had poor QoL. Bivariate analysis showed that comorbidities (PR = 1.61; 95% CI: 1.00-2.59), unhealthy dietary patterns (PR = 2.08; 95% CI: 1.21–3.56), and insufficient physical activity (PR = 2.70; 95% CI: 1.68–4.34) were significantly associated with poor QoL. In the multivariable analysis, insufficient physical activity remained the only independent determinant of poor QoL (aPR = 2.45; 95% CI: 1.51–3.97), whereas dietary patterns showed a borderline association (aPR = 1.72; 95% CI: 0.99–2.97). Insufficient physical activity was the only independent determinant of poor QoL among hypertensive patients. Promoting regular physical activity may improve QoL, while the independent role of dietary pattern requires further investigation. Keywords: Hypertension, Quality Of Life, Comorbidities, Dietary Pattern, Physical Activity